Fungal Infection and Aflatoxin Contaminationon Dried-Stored Spices - Kiki Nurtjahtja (Talenta Publisher, 2019)
A review regarding fungal infection and aflatoxin contamination by Aspergillus flavus during pre and post-tharvest handling on spices is presented. The results of research on spice storage management, physical and chemical treatments on dried spices before storage to prevent fungal infection are discussed.